EverBloomBags: Menghadapi Tantangan Lingkungan dengan Gaya, Inovasi, dan Kesadaran Berkelanjutan. - Amin, Moch. Akfi Muhadil; Febriansyah, Muhamat Alfian; Putra, Muzan Nalendra; Renaldy, Ach. Faisal; Radianto, Denny Oktavina (IAI Nasional Laa Roiba Bogor, 2023)
The issue of plastik waste has become an urgent global concern, with its negatve impacts on ecosystems and the environment becoming increasingly apparent. In an effort to address this issue, the United Nations has established 17 aspects of Sustainable Development Goals (SDGs). In this context, the innovative environmentally friendly bags from EverBloom Bags present an intriguing solution as part of achieving SDG 12 (Responsible Consumption and Production). Through the theory of sustainable consumption, we emphasize the importance of environmentally friendly products in fostering sustainable consumption patterns. By choosing eco-friendly bags, individuals can actively participate in reducing plastik waste and creating a better environment. The innovation of eco-friendly bags from EverBloom Bags represent a tangible step towards tackling the plastik waste issue. We illustrate the significance of adopting environmentally friendly product in achieving SDG 12, while providing practical solutions that contribute to environmental protection. With collective awareness and action, we can create positive changes in addressing current environmental issues and achieve sustainable development goals for a better future. Keyword : Plastic Waste, SDGs, Eco-Friendly Bags, Sustainable Consumption.